Severe Arthrographis kalrae keratomycosis in an immunocompetent Patient - Thomas, Bettina C.; Zimmermann, Stefan; Völcker, Hans Eberhard; Auffarth, Gerd U.; Dithmar, Stefan (Cornea, 2011)
Purpose: - To describe a severe case of keratomycosis caused by Arthrographis kalrae requiring repeated keratoplasty. - Methods: - A 42-year-old otherwise healthy soft contact lens wearer developed a unilateral central corneal ulcer. Treatment with topical and systemic voriconazole is described. - Results: - Repeated microbiological testing of ocular swabs (culture) initially yielded Candida albicans. Under treatment with topical clotrimazole, the ulcer progressed, and a corneal perforation required a keratoplasty à chaud. For prophylaxis, the patient received fluconazole systemically and continuous topical clotrimazole. However, in 2 weeks time, the mycotic infiltrates penetrated the corneal transplant and led to a second keratoplasty only 1 month after the first one. In the meantime, the microbiological analysis of the first keratoplasty revealed A. kalrae, which was sensitive to voriconazole. High-dose serum level-controlled systemic voriconazole and topical voriconazole were able to stabilize, but not eliminate the infection. About 1 year after the start of the voriconazole therapy, treatment had to be discontinued because of side effects. Mycotic infiltrates increased, and even an intracameral voriconazole injection could not prevent a third and a fourth keratoplasty. - Conclusions: - Ocular infection with A. kalrae is very rare. The microbiological differentiation of A. kalrae can be difficult. Because a broad spectrum of fungi is sensitive to voriconazole, the early topical and possibly systemic treatment is a reasonable therapeutic option when a mycotic infection of the eye is suspected, even before the causative fungus is identified.
Gesehen am 02.11.2022